Understanding History Through Tourism: The Benefits of Millennial Visitors to the Trowulan Site in Mojokerto Regency, Indonesia: Memahami Sejarah Lewat Pariwisata: Manfaat Kunjungan Wisatawan Millenial ke Situs Trowulan di Kabupaten Mojokerto Indonesia - Kinasih, Sri Endah; Nuruddi, Nuruddin; Firdaus, Aji Akbar; Aly, M. Nilzam; Ginting, Ina Veronica; Putri, Rahmah Fadiyah (Institut Pariwisata dan Bisnis Internasional, 2024)
The declining understanding and interest in historical studies among the millennial generation is a growing concern. Tourism has the potential to serve as a medium for enhancing historical comprehension, with the Trowulan site—an archaeological relic of the Majapahit Kingdom in Mojokerto Regency, East Java—offering a prime example. This study aims to analyze the activities and benefits of tourism based on historical heritage sites like Trowulan. A qualitative research method was employed, using a historical and descriptive-interpretative approach. Data were collected through literature reviews, field observations, and interviews conducted on-site. The findings indicate four key benefits millennial visitors gain from tourism activities at Trowulan: discovering physical evidence of the Majapahit Kingdom; increasing knowledge of Majapahit history through storytelling at the site; gaining new insights into Indonesia’s tangible and intangible cultural heritage; and fostering a deeper appreciation of the unique architectural achievements of Indonesia’s ancestors. The urgency of this study lies in addressing the declining interest among younger generations in cultural and historical education, which threatens the preservation of Indonesia's rich heritage. The novelty of this research is its focus on millennial visitors and its exploration of innovative strategies, such as integrating storytelling and interactive activities, to engage this demographic. This study contributes to the academic literature on heritage tourism by providing insights into the role of historical sites in promoting cultural and educational values. Practically, it offers actionable recommendations for tourism stakeholders to develop creative programs that ensure the sustainability and relevance of cultural heritage sites like Trowulan for future generations.